2015
DOI: 10.1155/2015/691290
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Layer-by-Layer Self-Assembly Clay-Based Nanocoating on Flame Retardant Properties of Sisal Fiber Cellulose Microcrystals

Abstract: The renewable cationic polyelectrolyte chitosan (CH) and anionic nanomontmorillonite (MMT) layers were alternately deposited on the surface of sisal fiber cellulose microcrystals (SFCM) via layer-by-layer (LBL) self-assembly method. The structure and properties of the composites were characterized by zeta potential, thermal gravimetric analysis (TGA), X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), Fourier transform infrared spectrometer (FTIR), microcalorimeter (MCC), and so fort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The coated LbL thus acts as interphase and improves the fiber/matrix interaction. LbL technique was found to improve the properties of natural fibers such as its strength [84,85], wettability [86], flame retardant efficiency [87], antibacterial property etc. Battegazzore et al [85] modify the surface of hemp fibers using chitosan and sepiolite (CH/SEP) and found significant improvement in the mechanical properties of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)/hemp fibers biocomposites.…”
Section: Layer By Layer Treatment (Lbl)mentioning
confidence: 99%
“…The coated LbL thus acts as interphase and improves the fiber/matrix interaction. LbL technique was found to improve the properties of natural fibers such as its strength [84,85], wettability [86], flame retardant efficiency [87], antibacterial property etc. Battegazzore et al [85] modify the surface of hemp fibers using chitosan and sepiolite (CH/SEP) and found significant improvement in the mechanical properties of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)/hemp fibers biocomposites.…”
Section: Layer By Layer Treatment (Lbl)mentioning
confidence: 99%
“…131 Wei et al also reported improvements in the thermal properties of highly flammable cellulose microcrystals (sisal fiber) after coating of chitosan and MMT layers. 132 Furthermore, the flame retardant properties of the MMT and rGO (MMT-rGO) membrane prepared by the vacuumassisted self-assembly process were reported by Liu et al 133 As shown in Figure 20a, when the MMT-G was subjected to an open flame, it burned in a flash due to the presence of residual oxygen groups. However, the flash was instantly selfextinguished with very slight deformations (Figure 20b).…”
Section: Responsivenessmentioning
confidence: 85%
“…Song et al observed that thinner MMT nanosheet membranes were more efficient in terms of the flame retardancy of PU foam . Wei et al also reported improvements in the thermal properties of highly flammable cellulose microcrystals (sisal fiber) after coating of chitosan and MMT layers …”
Section: Novel Properties and Potential Applicationsmentioning
confidence: 99%